PENGEMBANGAN HANDOUT BERGAMBAR DISERTAI PETA KONSEP PADA MATERI KINGDOM ANIMALIA UNTUK SEKOLAH MENENGAH ATAS (SMA) - Jefrianto, Jefrianto; Sudirman, Sudirman; Nerita, Siska (STKIP PGRI Sumbar, 2013)
ABSTRACT In teaching and learning process requires a media that is able to achieve the learning objectives. Forms of instruction a media used was teaching materials. One of teaching materials was a handout. A handout is a summary of the material that has been prepared by the teacher in the learning process. This handout was developed by using illustrations, drawings and concept maps that can develop student thinking in systematic framework. Based on explantion before the am of the study is to produce a concept map handout picture accompanied the kingdom animalia material to high school. This research is the development of a 4-D model of Thiagarajan (in Trianto, 2010:84) consist of define, design, develop and disseminate. The subjects of this study consist of two biology teachers and 20 studentss of class XI-IPA3 SMAN 2 Lengayang. The data of this study is primary data, the validity of test data and test result practicalities handout. Validity data and practicalities is in the form percentage is descriptive. The result of classified handout is valid (85,17%) by 5 validators and practical categories by teachers (87,78%) and by students categorized as very practical (90,13%). From this study produced a product concept map handout picture comes on the material kingdom animalia valid and practical.